2016
DOI: 10.5539/ijps.v8n4p1
|View full text |Cite
|
Sign up to set email alerts
|

The Caring-Uncaring Emotional (CUE) Inventory: A Pilot Study of a New Measure of Affective Psychopathy Traits

Abstract: <p>An affective dimension of psychopathy, e.g., callousness, lack of empathy, unemotional responsiveness, is essential to the study and understanding of psychopathy. It may be advantageous to have available brief measures of the affective dimension that may be utilized with adults and/or youths. The current study aims to provide preliminary validation of a new, brief, self-report measure of the affective dimension of psychopathy that may be suitable in the study of both adults and adolescents. A pilot st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Results of an exploratory factor analysis of the CUE were quite similar to the results of an EFA conducted in the initial pilot study (Semel, 2016), while several items were added to the CUE in the current study. As in the earlier study, results of the EFA supported a three-factor solution.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Results of an exploratory factor analysis of the CUE were quite similar to the results of an EFA conducted in the initial pilot study (Semel, 2016), while several items were added to the CUE in the current study. As in the earlier study, results of the EFA supported a three-factor solution.…”
Section: Discussionsupporting
confidence: 59%
“…The CUE was previously found (Semel, 2016) to be highly correlated with an expanded version of the Levenson Self-Report Psychopathy Scale (LSRP; Levenson et al, 1995) that was developed by Christian and Sellbom (2016). The CUE was most highly correlated with the Callous subscale of the expanded LSRP, and was highly correlated with the Egocentric subscale and moderately correlated with the Antisocial subscale.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The CUE Inventory was designed to measure affective traits of psychopathy. In two studies of community samples of adults (Semel, 2016(Semel, , 2017, the CUE was found to have high internal consistency reliability (α = .91 and .93, respectively). The CUE was found to have high correlations with an expanded, 36-item version of the Levenson Self-Report Psychopathy Scale (LSRP; Levenson, Kiehl, & Fitzpatrick, 1995) that was developed by Christian and Sellbom (2016), and with multiple subscale measures of callous affect from several established adult and youth psychopathy measures.…”
Section: Methodsmentioning
confidence: 99%
“…Five of the 11 items included in the APM Meanness scale were selected from the Caring-Uncaring Emotional (CUE) Inventory (Semel, 2016(Semel, , 2017. The CUE Inventory was designed to measure affective traits of psychopathy.…”
Section: Methodsmentioning
confidence: 99%